Disputed issues on Human Rights - Rovetta Klyver, Fernando (2016)
Disputed questions werw already raides in the medieval universities on issues that coulkd and needed to be debated. Human rights, as a modern invention, raise questions -assumed in this paper- whose need cannot be put off, but we suspect that not all law theories can define, substantiate and guarantee them.